Measurment procedure for metrological verification of the measuring channels of the automated process control system for monitoring the turbine generator parameters (СТК-ЕР-М) - Bossilkov, Krassimir; Tsvetelin, Georgiev; Nikolova, Elena; Radulova, Maya; Chunikhina, Tetiana (Technical University of Sofia Publishing House, 2023)
The report presents the methods for metrological verification of the measuring channels of the automated process control system for monitoring of the turbine generator parameters at Units 5 and 6 at of Kozloduy NPP.
Keywords: metrological verification; measuring channels; automated process control system